2007
DOI: 10.1080/07373930701227185
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Determination of Porosity Change from Shrinkage Curves of Deformable Materials

Abstract: Among the numerous models developed to predict the shrinkage of materials during drying, the model developed by Katekawa and Silva [1] gives a general relationship between shrinkage and porosity with a limited number of parameters such as initial density of the wet product, true density of the solid phase, and true density of the liquid phase. A graphical interpretation of this model is proposed to visualize the changes of porosity by comparing the experimental shrinkage curve with an ideal one. Four examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 27 publications
0
64
0
2
Order By: Relevance
“…It is clear from Figure 3 that, as expected, the thickness reduction was approximately proportional to the moisture content decrease. Madiouli et al (2007) commented on the fact that the choice of the drying process is significant in terms of final product shrinkage. Krokida and Brazilian Journal of Chemical Engineering Vol.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear from Figure 3 that, as expected, the thickness reduction was approximately proportional to the moisture content decrease. Madiouli et al (2007) commented on the fact that the choice of the drying process is significant in terms of final product shrinkage. Krokida and Brazilian Journal of Chemical Engineering Vol.…”
Section: Resultsmentioning
confidence: 99%
“…The second approach is more fundamental and based on mass and volume balance equations, applicable to the wide range of products and drying conditions. It was developed by Vacarezza (1975), Perez and Calvelo (1984), Zogzas et al (1994), Wang and Brennan (1995), Rahman et al (1996), Mayor and Sereno (2004), Katekawa and Silva (2004), and Madiouli et al (2007). Vacarezza (1975) proposed the model of linear relationship between shrinkage and moisture (ideal shrinkage), appropriate for convective drying of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not reveal fundamental relationship between moisture, shrinkage, density, and porosity based on geometrical considerations. The next contribution was made by Madiouli et al (2007) who proposed graphoanalytical method of porosity change determination from shrinkage curves of deformable materials. They analyzed all available expressions for shrinkage and concluded that bulk shrinkage (V/V 0 ) is the best indicator of the moisture loss (X/X 0 ) during the process of drying.…”
Section: Introductionmentioning
confidence: 99%
“…The real density was determined in a helium pycnometer, model 1000 Ultrapycometer of the brand Quantachrome Instruments. The shrinkage of samples was expressed in terms of the shrinkage coefficient V/V 0 , defined by Madiouli et al (2007). Moisture was determined in a chamber at 105 ± 5 °C for 24 hours.…”
Section: Characterizationmentioning
confidence: 99%
“…The kinetics of microwave drying was compared with those obtained in a lyophilizer and in convective drying by Prakash et al (2004). Zogzas et al (1994) and Madiouli et al (2007) presented different models for the representation of porosity, density and shrinkage of carrots during drying in a convective dryer. Krokida and Maroulis (1997) also suggested equations to determine the same properties of some fruits and vegetables, including carrots, during drying in several dryers, among them microwave dryers and lyophilizers.…”
Section: Introductionmentioning
confidence: 99%